Spanish seamen : inter-departmental correspondence - Carthy, A. E.
025a-0058-001 I.C.3. TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From A.E.CARTHY. Department INTERNATIONAL. To Mr H.V. TEWSON. Date 13th March, 1940. SUBJECT. SPANISH SEAMEN. I have been on the phone to Mr. Luzmore about our letter asking for the conditions attaching to the designation of the Spanish seamen as "friendly aliens". He tells me that the question is one outside his competence, but he is hoping to let us have a reply within 7/10 days. He added that he likewise hopes to get settled before Easter the question raised by us in December last (when we sent the list of seamen in our care) as to the regularisation of their position here. He hopes to be in a position to send a general letter, to obviate writing one for each seamen or port, differentiating between those who have been here from the beginning and those who have left in the meantime and who when they return will be subject to a fresh "condition of permit to land" (the formal endorsement by the Immigration Officer of Aliens' passports), which will separate them from the original groups, for whom we are responsible. 292/946/25a/58